2005
DOI: 10.1074/jbc.m500003200
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Preconditioning Ischemia on Ischemic Brain Injury through Down-regulating Activation of JNK1/2 via N-Methyl-D-aspartate Receptor-mediated Akt1 Activation

Abstract: Our previous studies have demonstrated that the JNK signaling pathway plays an important role in ischemic brain injury and is mediated via glutamate receptor 6. Others studies have shown that N-methyl-D-aspartate (NMDA) receptor is involved in the neuroprotection of ischemic preconditioning. Here we examined whether ischemic preconditioning down-regulates activation of the mixed lineage kinase-JNK signaling pathway via NMDA receptor-mediated Akt1 activation. In our present results, ischemic preconditioning cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 42 publications
(49 reference statements)
3
47
0
Order By: Relevance
“…36 Previous studies demonstrate that the NMDA receptordependent cellular signaling pathway is crucial in the protective effect of ischemia tolerance and that de novo protein synthesis is also required in this process. [37][38][39] Our results demonstrated that blocking NR2A completely abolished the neuroprotective effect induced by ischemic preconditioning. However, blocking NR2B further enhanced the neuroprotective effect.…”
Section: Discussionsupporting
confidence: 56%
“…36 Previous studies demonstrate that the NMDA receptordependent cellular signaling pathway is crucial in the protective effect of ischemia tolerance and that de novo protein synthesis is also required in this process. [37][38][39] Our results demonstrated that blocking NR2A completely abolished the neuroprotective effect induced by ischemic preconditioning. However, blocking NR2B further enhanced the neuroprotective effect.…”
Section: Discussionsupporting
confidence: 56%
“…16 -18 With ketamine exposure, the NMDA receptor is not activated and does not initiate downstream signaling. Ketamine alters Ca 2ϩ , 16 cAMP, 19 protein kinase C, 20 and mitogen activated protein kinase 21 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A key role for activation of the NMDA type of glutamate receptor during preconditioning by ischemia or OGD is well established (3)(4)(5)(6)(7)(8)(9)(10), although agreement is not complete (11,12). Moreover, transient non-lethal exposure to high dose glutamate or NMDA is sufficient on its own to also induce potent cross-tolerance to ischemia (13) or to OGD (1,6,14). To date, preconditioning achieved either by transient ischemia OGD or NMDA can require bringing neurons to the "brink of death" (1,14,15), a trait shared with some other preconditioning paradigms (2).…”
mentioning
confidence: 99%